Puteri Indonesia as A Business Strategy to Build Image of Mustika Ratu - Selena, Maria; Rudito, Bambang (Journal of Business and Management, 2014)
This research focuses on how Puteri Indonesia gives such a huge impact to Mustika Ratu in building and managing its brand image. Puteri Indonesia is a tool to add value in building image of Mustika Ratu through her activity and contribution, also the appearane includes clothes and the attributes, the activities in social field also in commercial, the ability in marketing communication as well as product knowledge which is surely well-exposed by mass media. It is done by participating method in the reign of Puteri Indonesia 2011.Keywords: Puteri Indonesia, Mustika Ratu, Puteri Indonesia 2011, Building image, Brand image, Marketing communication.